Neighborhood Fixer Uppers: Do Home Improvement Loans Influence Crime Across Race and over Time? - Gill, Lexi M. (American journal of criminal justice, 2023)
There has been a renewed interest in moving back into cities, which are close to business districts and offer affordable and unique housing. However, the available housing is limited and may require renovation as available housing close to the citycenter is often located in more economically disadvantaged neighborhoods. Property repairs and upgrading contributes not only to the improvement of individual owners’ properties, but the neighborhood overall. This influx of new residents and subsequent investment in housing can impact neighborhood crime, but the majority of the research on housing and crime has focused largely on home mortgage loans. The current study extends the housing investment literature by using an underutilized data source: home improvement and refinance loans, which signal physical improvement in the housing stock. This process may be different for neighborhoods that have a higher prevalence of minority residents as historically these residents have been subjected to inequitable lending practices. The current study examines how revitalization efforts in Cleveland, Ohio have influenced crime rates for the years 2007 through 2017 with special attention paid to the interplay of neighborhood racial composition and home improvement loans. Results from fixed-effects panel analysis reveal that home improvement loans are associated with an increase in property but not violent crime rates overall. Splitting neighborhoods into predominantly Black versus all other neighborhoods, however, results show that higher rates of home improvement loans are associated with lower violent crime rates, but the effect is tempered in Black neighborhoods. This suggests that the relationship between home improvement loans and violent crime is more complicated and varies by neighborhood composition.